2022
DOI: 10.1186/s12939-021-01589-x
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of healthcare costs in early life: a register-based study in the Netherlands

Abstract: Background Children with low socioeconomic status (SES) have an increased risk of a suboptimal start in life with ensuing higher healthcare costs. This study aims to investigate the effects of individual- (monthly household income) and contextual-level SES (household income and neighborhood deprivation), and perinatal morbidity (preterm birth and small for gestational age ((<10th percentile), SGA)) on healthcare costs in early life (0–3 years of age). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…In addition, the findings differ from some studies done in the United States of America and elsewhere where it was found that there is a positive relationship between SES and access to health care services and health spending [41]. On the other hand, studies done in the Netherlands found that households with low incomes had higher health expenditures compared with households with higher incomes [42,43]. The influence of social position could be clearer in the long term than in the short term.…”
Section: Discussioncontrasting
confidence: 91%
“…In addition, the findings differ from some studies done in the United States of America and elsewhere where it was found that there is a positive relationship between SES and access to health care services and health spending [41]. On the other hand, studies done in the Netherlands found that households with low incomes had higher health expenditures compared with households with higher incomes [42,43]. The influence of social position could be clearer in the long term than in the short term.…”
Section: Discussioncontrasting
confidence: 91%
“…Firstly, medical expenditure data revealed a positively skewed distribution, and thus they were converted to natural logarithm values. For all logistic regression models, medical expenditures were then dichotomized and the threshold was set at Q3 (the 75 th percentile), with Q1-Q3 in the low-cost group whereas Q4 in the highcost group, in accordance with previous research [34,35]. Furthermore, to assess how well the added comorbidity measures would improve the fitted models, we firstly calculated the loglikelihood ratio statistic G 2 [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining obesity in children aged 7-14 from different socioeconomic status in Turkey, it was stated that the prevalence of obesity was higher in students from middle and high socioeconomic status (9). In a recent study conducted in the Netherlands, it was emphasized that the children of families with low socioeconomic status had more frequent hospital admissions due to chronic diseases and growth retardation and therefore more health expenditures (10).…”
Section: Introductionmentioning
confidence: 99%